Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $A$ and $B$ are self-adjoint matrices. Why is it true that

$$Tr(A^2) \le Tr(Ae^{-tB}Ae^{tB})$$

for $t\in\mathbb R$, where $e^x$ denotes the matrix exponential?

share|cite|improve this question
up vote 6 down vote accepted

Since trace is invariant under conjugation, take $C$ such that $CBC^{-1}$ is diagonal, say $(\lambda_1,\cdots, \lambda_n)$. By replacing $A$ with $CAC^{-1}$, it suffices to show the inequality with $e^{tB} = diag(e^{\lambda_1},\cdots,e^{\lambda_n})$. It then suffices to check a few things

  1. $Tr(XY) = \sum_{i,j} X_{ij}Y_{ji}$, where $X,Y$ are two matrices that can be multiplied.
  2. $e^{-tB}Ae^{tB}$ has $(i,j)$ entry being $e^{\lambda_i - \lambda_j} a_{ij}$.
  3. Using 1 and 2, for $(X,Y) = (A,A)$ and $(A, e^{-tB}Ae^{tB})$, we need to show that $\sum_{i \neq j} 2a_{ij}^2 \leq \sum_{i \neq j} (e^{\lambda_i - \lambda_j} + e^{\lambda_j - \lambda_i}) a_{ij}^2$. (Here, we used the self adjointness of $A$ (in creating the squares), and that of $B$ (to make sure that the eigenvalues are real). This is clear by AMGM.
share|cite|improve this answer
+1 Nice answer. I tried to use the fact that the trace of the product of three symmetric matrices is invariant under any permutation (but failed :-(). – copper.hat Nov 5 '12 at 18:49
Did you mean replace $B$ with $CBC^{-1}$? I don't see how replacing $A$ in that way helps. – Potato Nov 5 '12 at 18:50
Both. I'm conjugating the matrices on both sides by $C$. – user27126 Nov 5 '12 at 18:50
Number $3$ is wrong. Try it with $A=\pmatrix{0&1\\1&0}$ and $\mathrm e^{tB}=\pmatrix{a\\&b}$. – joriki Nov 5 '12 at 18:51
Thanks. It's edited. – user27126 Nov 5 '12 at 18:55

Let $X,Y,Z$ be square matrices of the same size. Denote the commutator $[X,Y]=XY-YX$. Note that $\mathrm{Tr}[X,Y]=0$ and $\mathrm{Tr}(X[Y,Z])=-\mathrm{Tr}([X,Z]Y)$. In particular, $\mathrm{Tr}(X[X,Y])=0$.

Let $A_0=A$, $A_n=[A_{n-1},B]$ for each $n\ge 1$. Let $f(t)=\mathrm{Tr}(Ae^{-tB}Ae^{tB})$, which is an analytic function of $t$ with inifite convergence radius. By induction, it is easy to see that $f^{(n)}(t)=\mathrm{Tr}(Ae^{-tB}A_ne^{tB})$. In particular, $f^{(n)}(0)=\mathrm{Tr}(AA_n)$, so $$f(t)=\sum_{n=0}^\infty \frac{\mathrm{Tr}(AA_n)}{n!}t^n.$$

Let $a_{ij}=\mathrm{Tr}(A_iA_j)$ for $i,j\ge 0$. Then $$a_{i,j+1}=\mathrm{Tr}(A_i[A_j,B])=-\mathrm{Tr}([A_i,B]A_j)=-a_{i+1,j}.$$ In particular, $$a_{0,2n}=(-1)^na_{n,n}=(-1)^n\mathrm{Tr}(A_n^2),$$ and

Since both $A$ and $B$ are self-adjoint, by induction, it is easy to see that $A_n$ is self-adjoint when $n$ is even, and it is anti-self-adjoint when $n$ is odd. Therefore, The eigenvalues of $A_n$ are real when $n$ is even and are $0$ or pure imaginary when $n$ is odd. It follows that $a_{0,2n}\ge 0$ for every $n$.

Therefore, in the Taylor expansion of $f(t)$, the coefficients of the odd terms are zero, but the coefficients of the even terms are nonnegative. As a result, the conclusion follows from $f(t)\ge f(0)$.

share|cite|improve this answer
+1, very nice! :-) – joriki Nov 5 '12 at 20:15
@joriki: Thank you for editing and appreciation!:-) – 23rd Nov 5 '12 at 20:29

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.